Stage-specific embryonic antigen-4 is expressed in basaloid lung cancer and associated with poor prognosis - Gottschling, Sandra; Jensen, Katrin; Warth, Arne; Herth, Felix; Thomas, Michael; Schnabel, Philipp Albert; Herpel, Esther (The European respiratory journal, 2013)
Basaloid carcinoma represents a rare variant of nonsmall cell lung cancer (NSCLC), which has shown a poor prognosis in a number of studies. Although it is considered to derive from a pluri- or multipotent pulmonary stem cells, little is known about the expression and clinical significance of stem cell antigens in this variant. Stage-specific embryonic antigen-4 (SSEA-4) was analysed by immunohistochemistry in 38 patients with resected early-stage basaloid NSCLC who had a median follow-up of 72.9 months. The expression of SSEA-4 was related to clinico-pathological characteristics, to the expression of the adult stem cell antigens CD117, CD133 and breast cancer resistance protein 1 (BCRP1), and to prognosis. SSEA-4 was positive in 37% of the specimens and showed no association with clinico-pathological characteristics or the expression of adult stem cell antigens. Cox proportional hazards regression analysis revealed a 6.0-fold increased risk of relapse (p = 0.001) and a 4.2-fold increased risk of disease-related mortality (p = 0.017) in SSEA-4-positive patients, while SSEA-4-negative patients showed a prognosis comparable with that of other early-stage NSCLC. SSEA-4 is expressed in a fraction of basaloid NSCLC and is associated with poor prognosis.
Gesehen am 16.04.2018